Upaya Pencegahan Diare melalui Peningkatan Sanitasi Lingkungan dan Kebersihan Perorangan di RW 02 Kelurahan Kramat Pela Kebayoran Baru Jakarta Selatan - Muzakir, Haris; Harmani, Nanny; Nursyofia, Nasya; Hasanah, Aninda Putri; Nadhifah, Zahra Ariella; Lani Dasopang, Zahra Omas; Putra, Alfridho Pramandanu; Nurhalimah, Siti; Maghfira, Muthia; Roehan, Herma Avita (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Diarrhea remains a major health problem in South Jakarta, particularly in densely populated areas like RW 02 Kelurahan Kramat Pela, with key risk factors including poor environmental sanitation and low adherence to Clean and Healthy Living Behaviors (PHBS). This community service initiative aimed to enhance diarrhea prevention through education on environmental sanitation, personal hygiene, and demonstrations of proper handwashing with soap (CTPS) and waste composting. The Bryant method was used to prioritize interventions, identifying diarrhea as the primary issue (score 108). The program, conducted on April 28, 2025, involved 12 participants and employed lectures, discussions, and visual aids. Wilcoxon test results indicated no significant knowledge improvement (p-value=0.558), but increased awareness and active participation were observed. These findings suggest the need for improved methods, such as longer duration, sustained mentoring, and more interactive educational tools. The study underscores the importance of multidimensional and sustained approaches for behavioral change in diarrhea prevention.